2011
DOI: 10.7567/jjap.50.091603
|View full text |Cite
|
Sign up to set email alerts
|

n-Channel Organic Thin-Film Transistors based on Naphthalene–Bis(dicarboximide) Polymer for Organic Transistor Memory Using Hole-Acceptor Layer

Abstract: Undoubtedly, gadgets are devices for communication, entertainment and education as well for younger children. Children play with gadgets sitting or lying down at home and worse of all, apart from lacking in physical activity, they only communicate with the apps screen rather than with their parents. Besides parents, teachers are crucial in nurturing preschoolers during the early stage of their development. As a result, the current qualitative study interviewed 14 teachers to perceive their knowledge in gadget … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, these compounds tend to have low solubility in organic solvents, which makes the wet-coating of these materials difficult. Owing to the low solubility, their application to polymer materials are also limited only to naphthaleneimide moieties 7,8) except for a few cases of peryleneimide polymers prepared by vapor deposition-polymerization. 9) In this work, we explore electron-only devices (EODs) by vapor deposition of newly synthesized naphthalenediimide (NDI) derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…However, these compounds tend to have low solubility in organic solvents, which makes the wet-coating of these materials difficult. Owing to the low solubility, their application to polymer materials are also limited only to naphthaleneimide moieties 7,8) except for a few cases of peryleneimide polymers prepared by vapor deposition-polymerization. 9) In this work, we explore electron-only devices (EODs) by vapor deposition of newly synthesized naphthalenediimide (NDI) derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the memory operation could be interpreted in terms of writing, storing, repeated reading and erasing. Kaneto et al demonstrated OFET devices based on P3HT, a metal floating gate of Al or Ca, and a polyimide (PI) insulator film, which memory effects were also induced by light illumination in the cell having the floating gate with a decay time in the range of 1500 to 2500 s. Mohamad et al researched OTFT memory devices based on poly{[ N , N′‐bis (2‐octyldodecyl)‐naphthalene‐1,4,5,8‐ bis (dicarboximide)−2,6‐diyl]‐alt‐5,5′‐(2,2′‐bithiophene)} [P(NDI2OD‐T2)] n with additional P3HT films on a poly(methyl methacrylate) (PMMA) organic dielectric layer. In this case, P3HT films played a role as hole acceptor‐like storage layers resulted in reversible V th shift upon the application of external gate bias ( V bias ).…”
Section: Tethered Alkyl Substituted Polythiophenes Copolymers and Comentioning
confidence: 99%
“…[19] This memory device could be programmed at 50 V for 0. , has also been used in OFET memory devices; however, the device performance improved significantly only after using an additional poly(3-hexylthiophene) (P3HT) film on a poly(methylmethacrylate) (PMMA) dielectric layer for trapping charges. [22] OFET memory devices without any additional charge-trapping components do not have sufficient amount of charge trapping for two stable memory states. This low chargetrapping capability decreases the device performance and limits the commercial viability of OFET memory devices.…”
Section: Introductionmentioning
confidence: 99%